Attending to what you are doing: Neuropsychological and experimental evidence for interactions between perception and action - Humphreys, G; Riddoch, M; Linnell, K; Punt, D; Edwards, MG; Wing, A (Psychology Press, 2004)
What are the relations between perceptual selection (e.g. for object identification) and action selection (the selection of an appropriate action to an object)? We discuss four pieces of novel neuropsychological and experimental evidence indicating that perception and action interact in determining human performance. First, we show that action relations between stimuli constrain the amount of visual extinction present in neuropsychological patients. There is less extinction when objects are in the correct co-locations for action. In addition, action relations between objects can lead to the coupling of movements to objects in patients who otherwise show uncoupled actions to separate objects (in Balint's syndrome and in a case of motor extinction). Thus action relations between stimuli affect both perceptual selection (in cases of extinction) and action selection (in Balint's syndrome and motor extinction). Subsequently, we note evidence indicating that (1) action relations between objects and (2) actions to objects combine multiplicatively in their effects on visual selection. Finally, we introduce evidence from normal observers showing that action to an object can change the nature of the processes mediating visual selection. Perception and action are coupled when there are action relations between objects in the environment and when actions are made towards stimuli. © 2005 Psychology Press.